Gold(III) Complexes Activity against Multidrug-Resistant Bacteria of Veterinary Significance - Carlos Ratia; Sara Sueiro; Raquel G. Soengas; María José Iglesias; Fernando López-Ortiz; Sara María Soto (Antibiotics, 2022)
The emergence and spread of multidrug-resistant bacteria are a global concern. The lack of new antibiotics in the pipeline points to the need for developing new strategies. In this sense, gold(III) complexes (G3Cs) could be a promising alternative due to their recently described antibacterial activity. The aim of this study was to evaluate the antimicrobial activity of G3Cs alone and in combination with colistin against pathogenic bacteria from veterinary sources. Minimal inhibitory concentration (MIC) values were determined by broth microdilution and compared with clinically relevant antibiotics. Antibiofilm activity was determined by crystal violet staining. Combinations of selected G3Cs with colistin and cytotoxicity in commercial human cell lines were evaluated. Four and seven G3Cs showed antibacterial effect against Gram-negative and Gram-positive strains, respectively, with this activity being higher among Gram-positive strains. The G3Cs showed antibiofilm activity against Gram-negative species at concentrations similar or one to four folds higher than the corresponding MICs. Combination of G3Cs with colistin showed a potential synergistic antibacterial effect reducing concentrations and toxicity of both agents. The antimicrobial and antibiofilm activity, the synergistic effect when combined with colistin and the in vitro toxicity suggest that G3Cs would provide a new therapeutic alternative against multidrug-resistant bacteria from veterinary origin.